Estrategias metodológicas para el desarrollo de aprendizajes significativos, en el área de lengua y literatura, en niños y niñas del cuarto año de educación básica, de la escuela "Josefina Barba", de la parroquia Bilován, cantón San Miguel, provincia Bolívar, durante el periodo 2009 - 2010 - Erazo Galeas, Rita Germania (2011)
The present investigation on the Methodologic Strategies for the Development of Significant Learnings, in the Area of Language and Literature, in children and children of the Fourth Basic Year of Education, of the School "Josefina Beard", of the Parish Bilován, San Miguel Corner, Province Bolivar, During Period 2009-2010. The Educational Personnel to be in a Parish that does not fulfill all the standards for the academic development of methodologic strategies so that in children and children it is applied Significant learnings, associate that are by lack of didactic resources and does not tell on oriented advanced training courses the fortification and development of the intellectual, spiritual, critical capacity and of qualifying reflection what results in a comfort and turns pedagogical routine that it prevents to exceed schemes, adapted to the reality, from long time back and with limitantes levels in the processes of Education Learning. The fundamental objective is To include/understand to analyze to interpret messages with comparative aims to value the importance of the language, and to propose an interactive material that helps to develop to new expectations in the children and children. The guide of Methodologic Strategies in the class classroom becomes a very important resource that she puts to the teacher within reach of the daily life like tool to produce knowledge within reach of the students. This type of Guide, allows to improve the knowledge of a feasible way, obtained positive results in the Institution. The thesis is conformed by one first part introductoria, in which the subject considers, appear the antecedents, the problem, the justification, objectives, hypothesis and the operacionalización of variables; what corresponds upon presentment general of the work. Chapter I contains the theoretical frame; here it is developed to all the theory related to the investigation subject, considering the two variables of the hypothesis, to be able to determine the causes and effects of the problem and power to make the investigation to educational and the students; with the purpose of looking for alternatives of solution the problem. Chapter II is integrated by the methodologic frame; in that they are detailed: the type of investigation, the methods, the techniques to be used in the accomplishment of the work, as well as the population and sample that will be studied, to know the point of view with respect to the problem. Chapter III corresponds to the analysis of the results obtained in the investigation; here they appear the statistic in a picture and its graphical representation in pies, to come to analyze each one of the questions. What allows to make the verification of the hypothesis, conclusions and recommendations. Chapter IV talks about the proposal, in her considers the title, the introduction, the objectives that are wanted to obtain with the proposal, as well as the same development with the expositions that become; and finally the evidence and results of the application of the proposal, that is reflected in the annexes.